DIDACTIC CONSTRUCTING OF INFORMATION-TECHNOLOGY DISCIPLINES IN THE SYSTEM OF TRAINING FUTURE ARCHITECTS - Doroshenko Ю.О.; Osipa Т.В.; Osipa Л.В. (Journal of Information Technologies in Education (ITE), 2017)
The goal of this article is the presentation of didactic technology for constructing ITdisciplines for future architects in the professional training. Technology is based on competency approach and training methods of productive-technological activities. Didactic constructing of IT-discipline is a technological teacher’s activity for design,development and implementation in educational process the effective result-oriented didactic training system of information technology. The process of IT-discipline didactic constructing consists of three stages: the stage of setting goals and designing learning content; the stage of development IT-discipline’s didactic system; the stage of didactic analysis and content adjustment of IT discipline. Approbation the technology of didactic constructing for IT discipline is considered on an example of discipline " Informatics and computer modeling basics", which is taught to students training direction 191 " Architecture and town planning" in National Aviation University. Results of aprobation technology of didactic constructing IT disciplines in the educational process NAU show that the quality and effectiveness of teaching information technology of future architects are improved, level of their information competence is increased. Further directions of research are studies and the development of the technologies of diagnostic and the formal evaluation of the level of professional-informational competence of the future architects on the basis of competency tasks of professional orientation.